Designing a usable mobile application for field data collection - Moe, Kyaw Hlwan (My University, 2006)
The advent of mobile technology, Geospatial Information Systems (GIS) and convergence of voice and data over wireless networks have led to an explosion of a wide range of mobile applications. These applications include mobile internet browsers, handheld GPS navigation systems, Location Based Services (LBS), mobile workforce management systems, and so on. While much of the underlying technology is already available, there are challenges with respect to the usability of mobile applications. This project investigates the usability of a mobile application for field data collection in a utility industry. The purpose of the investigation is to gain a better understanding of the usability requirements for a mobile field data collection application but more importantly, how to meet these requirements using appropriate usability engineering techniques. A usage-centered design approach is used to design the user interface for the field data collection application. During this model-driven design process, the usability requirements are analyzed in terms of the user requirements, field data collection tasks and the operational context of fieldwork. An Underground Utility Closure (UUC) data sourcing work employed at a telecommunications utility is used as a case study for the field data collection work. The user interface is implemented as a functional prototype on a pocket computer and evaluated for usability in a field setting. It is envisaged that the usability requirements and design guidelines presented in this project will enable software engineers to meet the design challenges of usable mobile applications for field data collection and mobile computing in general.
Doctor of Science in Engineering - Engineering
Keywords: collection; data; application; mobile